(3JUeje MbjHI JYdjejI EdcJQhfjI bGFeI Ydi GdfXQjI GdHfGFjI hbjGS CKQgG Ydi GdJMUjd hGdegGQGJ hGdGJLGgGJ dOi WdGH GdUa GdKGfj GdKGfhj deGOI GdceHjhJQ (B/ s - (3gOi eHGQc SeGf eHGQcs; (3Ced YHOGdaJGM ShjOGf (B: s; (3MSf MSjfj LGeY (B: s ((3GdbGgQI (B: s (3gOi eHGQc SeGf eHGQc (B: s, 2014)
(3gOa gPG GdHMK eYQaI CKQ GSJNOGe GdMbjHI GdJYdjejI GdEdcJQhfjI GdbGFeI Ydi GdfXQjI GdHfGFjI aj JfejI GdJMUjd GdOQGSj hGdegGQGJ debQQ bGYOI GdHjGfGJ GdebQQ Ydi GdUa GdKGfj GdKGfhj hGdGJLGgGJ fMh GdMbjHI GdJYdjejI GdEdcJQhfjI cfXGe JYdjej eJcGed ddJYde GdPGJj (B. (3aJchfJ YjfI GdHMK ef (B60 (3WGdH ef WdGH GdUa GdKGfj GdKGfhj hef Ke Je JbSjege Edi eLehYJjf , JLQjHjI OQSJ HGSJNOGe GdMbjHI GdJYdjejI GdEdcJQhfjI h JchfJ ef (B30 (3WGdH (B: (3hVGHWI OQSJ HGSJNOGe GdWQjbI GdJbdjOjI hJchfJ ef (B30 (3WGdHs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3eYgO GdOQGSGJ h GdHMhK GdJQHhjI (B- (3bSe JcfhdhLjG GdJYdjes
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdJMUjd hGdegGQGJ hGdGJLGgGJs; (3GdfXQjI GdHfGFjIs; (3JUeje MbjHI JYdjejI EdcJQhfjIs